CLUSTER SYSTEM FOR AGGLOMERATION DEVELOPMENT - Ochilov, Khidoyatova, Akram Odilovich, Nigora Shorakibovna (THE INNOVATION ECONOMY, 2024)
This article proposes the formation of a cluster system for the development of agglomeration. The development of urban agglomeration, infrastructure development through clustering and effective indicators of economic and social activity are analyzed